Augmented Fibroblast Growth Factor-23 Secretion in Bone Locally Contributes to Impaired Bone Mineralization in Chronic Kidney Disease in Mice - Andrukhova, Olena; Schüler, Christiane; Bergow, Claudia; Petric, Alexandra; Erben, Reinhold G. (Frontiers in Endocrinology, 2018)
Chronic kidney disease-mineral and bone disorder (CKD-MBD) is a systemic disorder of mineral and bone metabolism caused by CKD. Impaired bone mineralization together with increased bony secretion of fibroblast growth factor-23 (FGF23) are hallmarks of CKD-MBD. We recently showed that FGF23 suppresses the expression of tissue nonspecific alkaline phosphatase (TNAP) in bone cells by a Klotho-independent, FGF receptor-3-mediated signaling axis, leading to the accumulation of the mineralization inhibitor pyrophosphate. Therefore, we hypothesized that excessive FGF23 secretion may locally impair bone mineralization in CKD-MBD. To test this hypothesis, we induced CKD by 5/6 nephrectomy in 3-mo-old wild-type (WT) mice and Fgf23-/-/VDR∆/∆ (Fgf23/VDR) compound mutant mice maintained on a diet enriched with calcium, phosphate, and lactose. Eight weeks postsurgery, WT CKD mice were characterized by reduced bone mineral density at the axial and appendicular skeleton, hyperphosphatemia, secondary hyperparathyroidism, increased serum intact Fgf23, and impaired bone mineralization as evidenced by bone histomorphometry. Laser capture microdissection in bone cryosections showed that both osteoblasts and osteocytes contributed to the CKD-induced increase in Fgf23 mRNA abundance. In line with our hypothesis, osteoblastic and osteocytic activity of alkaline phosphatase was reduced, and bone pyrophosphate concentration was ⁓2.5-fold higher in CKD mice, relative to Sham controls. In Fgf23/VDR compound mice lacking Fgf23, 5/6-Nx induced secondary hyperparathyroidism and bone loss. However, 5/6-Nx failed to suppress TNAP activity, and bone pyrophosphate concentrations remained unchanged in Fgf23/VDR CKD mice. Collectively, our data suggest that elevated Fgf23 production in bone contributes to the mineralization defect in CKD-MDB by auto-/paracrine suppression of TNAP and subsequent accumulation of pyrophosphate in bone. Hence, our study has identified a novel mechanism involved in the pathogenesis of CKD-MBD.